The Torre do Tombo: from Crown Archive to National Archive: Institutional contexts based on enacted legislation (16th century-2012) - Rodrigues, Abel (2024)
This text aims to identify and define the chronological evolution of Torre do Tombo, first as the Crown Archive and then as the National Archive, presenting the official legislation enacted between the 16th century and 2012 by successive sovereign bodies. We established five main contexts: Between the end of the Middle Ages and the end of the Ancien Regime: the king, the dispatch and the archives of the Crown (16th-18th centuries); The transformation imposed by the Constitutional Monarchy: the National Archives (1820-1910); The First Republic: centralisation and decentralisation (1910-1926); The Military Dictatorship and the Estado Novo (1926-1974); From 25th April to nowadays: present and future of a National Archive (1974-2012). We intend to establish the successive political and administrative frameworks of the institution and, above all, to contextualise the evolution of its functions and activities, which are crucial to understanding the forms of information production and acquisition as well as the archival history of the fonds it currently holds.